Fiscal policy and private consumption: Saving decisions: Evidence from Finland - Anne Brunila (Bank of Finland, 1996)
The paper presents a theoretical model of private consumption that emcompasses both the conventional (Keynesian) view of fiscal policy and the Ricardian debt neutrality hypothesis.The effects of fiscal policy on private consumption are analyzed in an extended framework built on Blanchard's stochastic model of intertemporal optimization with finitely lived consumers, in which private consumption depends on expected lifetime wealth.The model also nests various hypotheses concerning the relationship between public spending and private consumption.Empirical analysis is based on the Finnish annual data from 1960-1995 and uses the nonlinear instrumental variable GMM estimator.The tests cannot reject the hypothesis that consumers are Ricardian.Moreover, the results suggest that in the consumers' utility functions, government consumption is a substitute for private consumption.
URN:NBN:fi:bof-20140807317
Keywords: 330; private consumption; private saving; fiscal policy; planning horizon